2004
DOI: 10.1152/nips.01461.2003
|View full text |Cite
|
Sign up to set email alerts
|

Why Do We Not All Have Proteinuria? An Update of Our Current Understanding of the Glomerular Barrier

Abstract: The key question is not why some patients have proteinuria but rather why not all people have it. In the present review, we will present an update on the glomerular barrier after the recent breakthroughs in podocyte biology. In particular, we will discuss the role of the endothelium, which seems to be a neglected part of the glomerular membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 18 publications
2
81
0
1
Order By: Relevance
“…More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 73%
“…More recently, focus has shifted to the podocytes, since several novel proteins in the podocyte slit diaphragm have been found to be important for the barrier function [1][2][3]. In addition, we have suggested a role for the glomerular endothelial cell glycocalyx [4][5][6][7][8][9][10], an idea supported also by others [11,12].…”
Section: Introductionsupporting
confidence: 73%
“…The unmodified antibodies, an scDb of 55 kDa and an scFv of 28 kDa, were rapidly cleared from circulation with terminal half-lives of 1.3 h for the scDb and 0.6 h for the scFv. In a previous study of the same scDb used here, we showed that this is mainly due to rapid renal clearance (22), reflected also by the Stokes radius of only 2.6 nm, which allows almost unhindered passage through the glomerular filtration barrier (23). Only marginal effects on the half-life was seen for the SpA EZ4 and the PpL C4 * fusion proteins with 2-3-fold increased half-lives.…”
Section: Discussionmentioning
confidence: 52%
“…Recently, we developed a novel leptin version by fusing a polypeptide comprising 600 Pro, Ala and Ser (PAS) residues to the N-terminus of the murine protein [11]. The PAS moiety adopts a random coil conformation and expands the average diameter of the fusion protein beyond the pore size of the kidney filtration barrier [11][12][13].…”
Section: Introductionmentioning
confidence: 99%